2022
DOI: 10.1371/journal.pone.0275115
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and pregnancy profile of complicated malaria in 982 pregnancies in Kinshasa

Abstract: Introduction Malaria is associated with high morbidity during pregnancy. Homozygous sickle cell pregnant women are even more exposed during complicated malaria. The objective of the study was to evaluate the maternal and fetal morbidity of homozygous sickle cell pregnant pregnant women with complicated malaria. Methods We conducted a retrospective case-control study of 982 pregnancies in sickle cell pregnant women, during which a group of sickle cell pregnant women who received antimalarial chemoprophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Genetic variation in the production of F-cells has been shown to allow female sickle cell patients to have more HbF than their male counterparts [25,26]. In addition, HbF levels are associated with the clinical severity of sickle cell disease, according to two studies conducted in the Democratic Republic of the Congo [27][28][29]. A Nigerian study also found a significant inverse correlation between sickle cell disease severity and HbF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in the production of F-cells has been shown to allow female sickle cell patients to have more HbF than their male counterparts [25,26]. In addition, HbF levels are associated with the clinical severity of sickle cell disease, according to two studies conducted in the Democratic Republic of the Congo [27][28][29]. A Nigerian study also found a significant inverse correlation between sickle cell disease severity and HbF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection, the use of specific vaccines, prophylaxis with penicillin and especially the use of hydroxy urea have improved the quality of life and life expectancy of sickle cell patients [14][15][16][17]. This is why, currently in sub-Saharan countries, the association between SCA and pregnancy is frequent [9,18]. Indeed, this high frequency of the association SCA and pregnancy is due to the fact that fertility is preserved in sickle cell patients.…”
Section: Introductionmentioning
confidence: 99%